PERBEDAAN TINGKAT PEMAHAMAN AKUNTANSI MAHASISWA BERDASARKAN LULUSAN PADA MAHASISWA SEMESTER II TAHUN ANGKATAN 2017 PRODI AKUNTANSI UNIVERSITAS MUARA BUNGO - Naela Mikya Lulfaizahni (Pt. Anagata Sembagi Education, 2024)
This research hopes to prove whether there are differences in understanding of accounting material from different school backgrounds. Research object at the Faculty of Economics, Muara Bungo University. In this study, the population used as the population in this study were students majoring in Accounting, totaling 62 second semester students at Muara Bungo University (UMB). This research uses quantitative descriptive data analysis outlined in the form of a frequency table. The scoring technique that will be used is a Likert scale to assess respondents' questionnaire answers. The definition of accounting according to the American Accounting Association is a process of identifying, measuring and reporting economic information to enable clear and firm research and decisions for those who use the information. The results of this research show that there is a significant difference in the level of understanding of assets between students from vocational school majoring in accounting, high school majoring in social studies and Madrasah Aliyah General. Assets, There is a significant difference in the level of understanding of obligations between students from the Accounting Department Vocational School, the Social Sciences Department High School and the General Madrasah Aliyah. Obligations, and There is a significant difference in the level of understanding of capital between students from the Accounting Department Vocational School, the Social Sciences Department High School and the General Madrasah Aliyah Equity.